Hämophilie und Knorpel - Seuser, A. (Hämostaseologie, 2012)
It is not the blood alone! Increased loading destroys cartilage and leads to arthrosis. Reduced mechanical stimulation leads to reduced cartilage nutrition and to cartilage degeneration, which leads to arthrosis. We know about the existence of functional disturbances that occur in early childhood before any structural changes are diagnosed. This is typical for haemophilia. Those disturbances and the way movement is disturbed has a strong influence on the loading of cartilage. This involves acceleration peaks, disturbed load distribution with reduction of contact area and a change of vector direction, which leads to increased cartilage loading. The disturbed function can be analysed very early with motion analysis. Easy physiotherapeutical interventions are able to optimise function again. On top of that we have a loss of muscle contraction pattern. Around the knee joint it is the weakening of the vastus medialis and the shortening of the knee flexors. The ankle joint suffers from a weakening of the tibialis anterior and a shortening of the calf muscles. During progression of the disease there will be a shortening of the weakened muscle and a weakening of the shortened muscle as well. Kinetic superficial EMG is able to quantify the status of the muscles and enables us to prescribe an individual therapy. Subclinical influences like microbleeds, in the beginning silent synovitis, later chronic synovitis, silent symptoms and overprotection are the cause of the functional overloading of the cartilage in patient with haemophilia. Silent symptoms can be discovered by clinical examination. Again this leads to the opportunity of a symptomatic therapeutic approach. All those facts could be the reason why there is an increasing incidence of haemarthrophathy of the ankle joint, even in patients with mild haemophilia in spite of adequate factor substitution.
Keywords: Haemophilia; cartilage; 3D motion analysis; EMG; haemarthropathy